Soil Engineering - Spangler, Merlin Grant (Pennsylvania : International Textbook Company, 1960)
Annotation In the last forty years, at least fifty books have been written on the subject of soil mechanics, most of them textbooks. Only a few touch on practical applications. Soil Engineering: Testing, Design, and Remediation supplies the information needed to fill the gap between textbook learning and practical know-how.When engineers deal with major projects, such as the Teton Dam or the Leaning Tower of Pisa, they need high-tech solutions. More often than not, however, they deal with the foundations for warehouses, schools, medium-rise buildings, and residential structures, projects that need low-tech solutions. Ninety percent of the time consulting engineers don't require mathematical treatment or computer analysis, they require experience.Soil engineering problems cannot be resolved with textbook information alone. This book provides the practical meaning of the different aspects of soil mechanics, the use of unconfined compression test data, the meaning of consolidated tests, the practical value of lateral pressure, and more. In addition to the technical aspects of foundation investigation, in the real world the shadow of litigation looms over every consultant's head. The author covers legal issues in detail.After several years in foundation investigation most consultants realize that soil engineering is a combination of art and science. Soil Engineering: Testing, Design and Remediation demystifies this connection and supplies real-world examples of practical applications. This hands-on, ready reference will be essential tool for any consultant working in the field.
Includes index
Trade
Keywords: Soil engineering